The Effectiveness of an Emergent Literacy Intervention for Teenage Parents. Issue 1 (January 2016) - Scott, Amy; van Bysterveldt, Anne; McNeill, Brigid
Abstract : This study determined the effectiveness of an experimental emergent literacy intervention, targeting teenage mothers attending an educational facility. Using a pretest/posttest research design, 27 participants completed a 7-week intervention based in the classroom, targeting a range of emergent literacy skills that they could utilize when reading with their children. Assessment tracked changes in the type and frequency of participants' reading behaviors demonstrated during videoed shared reading interactions with their young children, as well as changes to aspects of the home literacy environment. Data analysis was completed by an independent coder who was blinded to the group (research or comparison) and time point (pre or post) allocation. Results indicated significantly greater frequency of vocabulary, questioning, and book/print features-focused reading behaviors from pretest to posttest. No changes were observed in reading behaviors relating to letter/sound features. The data provide evidence to support the efficacy of an emergent literacy intervention in changing the shared reading behaviors of teenage mothers. Abstract : Supplemental Digital Content is Available in the Text.